The Relationship between Bank Competition and Bank Risk in China——Under the Background of Economic Development - Wang, Qiuting (2017)
Abstract: This dissertation aims at offering new insight into the relationship between bank competition and bank risk in China`s financial market. When we discuss the relationship of them, there are always two main points of view in academia. One is “Competition-Fragility theory” which thinks fierce competition would weaken bank`s monopoly power, leading to lower profits obtained by banks, the other is “Competition-Stability theory” that argues competition promotes the stability of banks, while concentration leads to the fragility of it. There are also neutral opinions that combine the viewpoints of these two theories or oppose these two theories doubting the existence of stability. To examine their relationship in China, I will use two indices —Lerner Index and Boone Index. The former is usually used to describe the degree of competition in markets, while the latter can represent the relationship between competition and risks. By using data of listed banks from Wind database, we conclude that from 2006 to 2015, competition in China`s banking industry is not fierce yet probably because of the restrictions imposed by the Chinese government and the reform that temporarily ended in the end of 2007. We then explore such relationship in terms of different kinds of banks and two periods. Performance of state owned banks has little relation to competition on the financial market. In other words, the risk of state owned banks is not mainly resulted by competition from peers. It perhaps comes from restrictions imposed by government or immature management system. Results of joint-equity banks and city commercial banks which are similar to state owned banks show little relationship between the performance of joint-equity banks and competition. Finally, we study this issue by separate ten years into two five years. We examine the relationship between the performance of all kinds of banks and competition in two periods. In the first period, ROA presents strongly positive relationship to marginal costs. Such phenomenon can be explained by the fast growth of China`s economy and city commercial banks. In the second period, they had a strong positive relationship with t-test equal to 1.89. In this period, for every 1% increase in total loans, the cost is increased by 5.7%. But we have to admit that financial market in China is far away from mature so some research conclusions are not applicable to other countries, even to other eras of China.